2018
DOI: 10.1177/000313481808400619
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Surgical Bootcamps to Teach Core Entrustable Professional Activities to Senior Medical Students

Abstract: To promote residency preparedness, the Association of American Medical Colleges defined 13 core entrustable professional activities for entering residency (CEPAERs), which represent tasks that students should be able to perform on day one of residency. At the authors’ institution, a four-week surgery boot camp course is offered to senior medical students, which may provide an effective mechanism for teaching the CEPAERs. Nine senior students participating in a surgery boot camp course were subjected to pre- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…1 Some of the design in these courses has been aimed at helping students achieve core skills or competencies as defined by the Association of American Medical Colleges (AAMC) or Accreditation Council for Graduate Medical Education (ACGME). 2,3 Many other specialties have begun to develop such prep courses as well, and students who have completed these courses recognize their benefit and feel all students should participate in such preparation. 4 The boot camps taught at different institutions vary in their duration, from one day to four weeks, but are similar in the areas of focus, including basic medical and technical knowledge needed for intern year.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some of the design in these courses has been aimed at helping students achieve core skills or competencies as defined by the Association of American Medical Colleges (AAMC) or Accreditation Council for Graduate Medical Education (ACGME). 2,3 Many other specialties have begun to develop such prep courses as well, and students who have completed these courses recognize their benefit and feel all students should participate in such preparation. 4 The boot camps taught at different institutions vary in their duration, from one day to four weeks, but are similar in the areas of focus, including basic medical and technical knowledge needed for intern year.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, there has been a surge of residency readiness programs implemented as part of the fourth-year medical school curriculum or as part of the transition to residency. 8 While the type and quality of these programs have substantial variability, drawing mixed results on their utility, 2830 there is some evidence from the current study that residents who attended prior readiness programs were less likely to select potentially harmful actions (3% lower than residents who did not attend prior readiness programs); however, the overall rate of harmful decisions remained high (15% overall). While current results are useful in pinpointing shortcomings, additional research is needed to fully identify specific relationships between the curricular content and experiences of bootcamps that facilitate the clinical decision-making skills of entering residents.…”
Section: Discussionmentioning
confidence: 68%
“…Several lines of evidence have suggested that boot camps represent an effective and useful means of teaching [ 26 , 27 ]. Despite knowledge of this success, few studies have investigated the usefulness of delivering exercise education via boot camps for individuals with PD.…”
Section: Introductionmentioning
confidence: 99%